2012
DOI: 10.5038/2375-0901.15.1.7
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Flexible Transport Services in Enhancing Rural Public Transport Provision

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 19 publications
0
56
0
Order By: Relevance
“…A survey by Koffman [2] implied that most flexible transit services are provided without service planning or design guidelines. The investigation by Velaga et al [3] in rural Scotland also confirmed the dilemma in the planning and implementation of specific flexible transit programs. When planners design such systems, they are not sure whether to adopt a fixed-route policy or a flex-route policy in a specific service, and the "switch" between the two policies still puzzles transit operators during daily operation.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…A survey by Koffman [2] implied that most flexible transit services are provided without service planning or design guidelines. The investigation by Velaga et al [3] in rural Scotland also confirmed the dilemma in the planning and implementation of specific flexible transit programs. When planners design such systems, they are not sure whether to adopt a fixed-route policy or a flex-route policy in a specific service, and the "switch" between the two policies still puzzles transit operators during daily operation.…”
Section: Introductionmentioning
confidence: 83%
“…In their operating environment, all door-to-door demands can be accepted and served without considering the constraint of a predetermined slack time. The work by Velaga et al [3] confirmed that one of the challenges in providing flexible transit services is that the varying travel demand in low-demand areas is difficult to predict. In addition, in practical use, demand responsive connectors generally require a fixed schedule [2], which is usually designed for the coordination of the major transit and the feeder transit.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among these, route deviation is by far the most common form (up to 63.9%), while point deviation only accounts for 16%. One of the main factors 2 Journal of Advanced Transportation hindering the widespread use of point deviation service is the sophisticated support systems required to schedule the curb-to-curb requests [6]. However, with the rapid development of intelligent transportation systems, point deviation is becoming a promising operating policy from a long-term perspective.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of medical care this can apply to a transport of patients, whose destination is always the same single practice, central health center or hospital [44]. Since underage and elderly persons were identified as having major restrictions concerning rural mobility web based ride sharing could be a possible solution [45]. For this purpose the assumed substandard internet access of the elderly needs reflection.…”
Section: Discussionmentioning
confidence: 99%